Novel AlGaN/GaN Omega-FinFETs with Excellent Device Performances - Im, Ki-Sik; Won, Chul-Ho; Seo, Jae Hwa; Kang, In Man; Vodapally, Sindhuri; Lee, Yong Soo; Lee, Jung-Hee; Kim, Yong-Tae; Cristoloveanu, Sorin (2016 46TH EUROPEAN SOLID-STATE DEVICE RESEARCH CONFERENCE (ESSDERC), 2016)
AlGaN/GaN nanowire omega-FinFETs have been fabricated and characterized. Tetramethylammonium hydroxide (TMAH) lateral wet etching and atomic layer deposited (ALD) HfO2 sidewall spacer result in very sharp vertical edges and fin widths from 200 nm down to 30 nm. Omega-gate structure exhibits excellent gate controllability and separates the channel from the underlying thick GaN buffer layer, which leads to excellent device performances: maximum drain current of 480 mA/mm, maximum transconductance of 370 mS/mm, extremely low leakage current of similar to 10(-11) mA, subthreshold swing of 57 similar to 63 mV/decade, close to the theoretical limit, very high I-on/I-off ratio of similar to 10(10), and breakdown voltage of similar to 220 V. An increase in R-on was observed due to current collapse at the drain lag condition, but the saturation current was fully recovered at higher drain voltage. This is because the current spreads from the narrow fin to the wide access region and the gate overlapped configuration prevents the trapping at the surface and in the buffer layer, which leads to the reduced access resistance in between the gate-to-source and gate-to-drain compared with the planar AlGaN/GaN MISHFET.